THE DEVELOPMENT OF LABORATORY-BASED EARTH AND SPACE SCIENCE LEARNING MODEL TO IMPROVE SCIENCE GENERIC SKILLS OF PRE-SERVICE TEACHERS (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
This study focuses on the improvement of prospective teachers’ science generic skills in learning for earth and space sciences subject using a laboratory-based model. Research methods were Research and Development used mixed methods design, i.e. Embedded Experimental models. The results showed that the structure of the learning using laboratory-based model consists of four stages, namely engagement, exploration, explanation, and elaboration; with details on description of natural phenomena, the identification of questions, linking concepts with practical topic; modeling, training, exploration, interpretation of data, conclude, and communicate the procedures and results of the investigation. Moreover, the ability of science generic skills of teacher candidates was low at 52.50%. In addition, the profile of lecturer performance in learning reached 55%. Also, the condition of the learning environment is generally sufficient in supporting the development of laboratory activities, for example: a comfortable laboratory room for conducting the practicum. Next, 75% student agreed that for understand the material; it needs a practice in lab. As many as 70% of students agreed that practicum will increase students' understanding, although students also agreed that clarification is still required by lecturers (80%). Furthermore, 69% of the students found the materials of Earth and Space Sciences ismore attractive than other materials, although 78% said material of Earth and Space Sciences is fairly complicated and abstract. The interest of students to the material of Earth and Space Sciences is because these materials can foster curiosity (88%) as well as providing benefits to their daily life (90%). Finally, three out of four students agreed that the science generic skills can develop the ability of scientific work and critical thinking.